Experimental and simulation study of fluidization behavior of palm biomass in a circulating fluidized bed riser - Hussain, A. (2013)
Circulating fluidized bed combustion (CFBC) technology is being used for few decades to burn biomass wastes while meeting the stringent emission standards; however, much is needed to be understood about the complex flow patterns that are encountered. This work is aimed at understanding the major fluidization characteristics in a CFB loop for palm shell waste powders. Effects of inlet air on the fluidization behavior were experimentally investigated. The voidage of the bed material was found to be a function of axial distance above the distributor. The CFD modeling has also been done to quantify the riser exit effects. The flow was simulated using the "algebraic slip mixture (ASM)" model. In the simulation results the deviation of velocity contours owing to variation in riser exit geometries is discussed. It was found that the influence is found to be significant in the upper region of the riser column and the velocity contours are also swayed by the exit geometry. Â© 2013 American Chemical Society.